Analyzing the Concept of Components in the Brechó-VCM Approach through a Sociotechnical and Software Reuse Management Perspective - Santos, Rodrigo Pereira dos; Werner, Cláudia Maria (Anais do Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software (SBCARS); 2010: Anais do IV Simpósio Brasileiro de Componentes, Arquiteturas e Reutilização de Software, 2010)
This paper analyzes the concept of components in Software Engineering (SE) through a sociotechnical approach. Based on a ranking of critical elements related to Component-Based SE, a study with experts concludes that components are potential assets in local and collaborative scenarios. This fact motivated an analysis of a value-based component market approach called Brechó-VCM considering its adherence to the Reuse Management Process, part of MPS Quality Model, in order to treat some critical elements in a reuse-based environment. The results reinforce that SE community needs to learn with the case of components aiming to understand SE as a sociotechnical construction.